Hallucinations after Valproic Acid Withdrawal - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Child psychiatrists and neurologists in Utrecht, The Netherlands report case histories of 2 girls, ages 4 and 12 years, with a history of epilepsy who developed hallucinations after withdrawal of valproic acid (VPA).